Reactivity of IgE to the allergen hyaluronidase from Polybia paulista (Hymenoptera, Vespidae) venom - Justo Jacomini, Debora Lais [UNESP]; Gomes Moreira, Susana Margarida; Campos Pereira, Franco Dani [UNESP]; Zollner, Ricardo de Lima; Brochetto Braga, Marcia Regina [UNESP] (Elsevier B.V., 2014)
To date, there are no allergenic extracts or components available in Brazil to diagnosis and treatment of patients with venom allergy from social wasp (Vespidae Family; Polistinae Subfamily) despite of the great number of existing species. We evaluated the immunogenic potential of the Hyal recombinant protein (Pp-Hyal-rec) which was expressed in an insoluble form in comparison with the allergenic native protein (Pp-Hyal-nat) for recognition of immunoglobulin E (IgE).in the serum of allergic patients to venom of the endemic social wasp Polybia paulista from Sao Paulo State, Brazil. Hyal cDNA from the venom of the social wasp P. paulista (Pp-Hyal) (GI: 302201582) was cloned into the expression vector pET-28a in Escherichia coli DE3 (BL21) cells. Solubilization and purification of Pp-Hyal-rec from inclusion bodies were performed using Ni2+ affinity chromatography (Ni-NTA-Agarose) under denaturing conditions. Both the native (Pp-Hyal-nat) and the recombinant (Pp-Hyal-rec) purified allergens were used for Western blotting to assess the levels of Pp-Hyal-IgE specific in the serum of 10 patients exclusively reactive to the venom of the social wasp P. paulista. The immune sera specifically recognized the band corresponding to the Pp-Hyal-rec protein (40 kDa) at a higher intensity than the native allergen (39 kDa). The sera recognized other proteins in P. paulista crude venom extract to a lesser extent, likely corresponding to other venom allergens such as phospholipase (34 kDa), Antigen 5 (25 kDa), and proteases. The recognition pattern of the immune sera to the Pp-Hyal-rec allergen strongly suggests that this recombinant antigen could be used for developing a diagnostic allergy test as well as for specific immunotherapy (IT). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Polybia paulista; Venom; Allergen; Recombinant hyaluronidase; Immunoglobulin E (IgE); Cross-immunoreactivity